Residential proximity to livestock farms is associated with a lower prevalence of atopy. Issue 6 (30th April 2018) - Borlée, Floor; Yzermans, C Joris; Krop, Esmeralda J M; Maassen, Catharina B M; Schellevis, François G; Heederik, Dick J J; Smit, Lidwien A M
Abstract : Objectives: Exposure to farm environments during childhood and adult life seems to reduce the risk of atopic sensitisation. Most studies have been conducted among farmers, but people living in rural areas may have similar protective effects for atopy. This study aims to investigate the association between residential proximity to livestock farms and atopy among non-farming adults living in a rural area in the Netherlands. Methods: We conducted a cross-sectional study among 2443 adults (20–72 years). Atopy was defined as specific IgE to common allergens and/or total IgE ≥100 IU/mL. Residential proximity to livestock farms was assessed as 1) distance to the nearest pig, poultry, cattle or any farm, 2) number of farms within 500 m and 1000 m, and 3) modelled annual average fine dust emissions from farms within 500 m and 1000 m. Data were analysed with multiple logistic regression and generalised additive models. Results: The prevalence of atopy was 29.8%. Subjects living at short distances from farms (<327 m, first tertile) had a lower odds for atopy compared with subjects living further away (>527 m, third tertile) (OR 0.79, 95% CI 0.63 to 0.98). Significant associations in the same direction were found with distance to the nearest pig or cattle farm. The associations between atopy and livestock farm exposure were somewhat stronger in subjects who grew up on a farm. Conclusions: Living in close proximity to livestock farms seems to protect against atopy. This study provides evidence that protective effects of early-life and adult farm exposures may extend beyond farming populations.